1991
DOI: 10.3758/bf03333957
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in storage and retrieval: A multinomial modeling analysis

Abstract: An experiment is reported that examined the memory differences between 23 college students (21-41 years old) and 23 elderly adults (64-92 years old). Both groups memorized lists ofcategorically related words over a series of three study-test trials in a free-recall design. Consistent with prior research on aging effects, the elderly subjects performed more poorly on the number of words recalled, the number of categories recalled, the number of items recalled per category, and the amount of category clustering.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 22 publications
(21 reference statements)
2
29
1
Order By: Relevance
“…This research met with some criticism due to the choice of retrieval indices used and the fact that an external verbal memory criterion was not utilized to validate the retrieval indices in the study (Delis et al, 2000). Nevertheless, the use of recognition–free-recall discrepancies has resulted in mixed findings in other studies as well (see Riefer & Batchelder, 1991). It has been suggested that results based on such discrepancies can be misleading, as they reflect multiple processes.…”
Section: Retrievalmentioning
confidence: 99%
“…This research met with some criticism due to the choice of retrieval indices used and the fact that an external verbal memory criterion was not utilized to validate the retrieval indices in the study (Delis et al, 2000). Nevertheless, the use of recognition–free-recall discrepancies has resulted in mixed findings in other studies as well (see Riefer & Batchelder, 1991). It has been suggested that results based on such discrepancies can be misleading, as they reflect multiple processes.…”
Section: Retrievalmentioning
confidence: 99%
“…The pair-clustering model is one of the best analyzed members of the family of multinomial models (e.g., Batchelder & Riefer, 1986Riefer & Batchelder, 1991). It is based on a free-recall task in which participants are presented with a list of words that are related by categories.…”
mentioning
confidence: 99%
“…(2) in the form of % 1 , % 2 or (1&% 1 ), (1&% 2 ). Models with the above characteristics have been used in cognitive psychology research, especially in human memory studies (Riefer 6 Rouder, 1992;Riefer 6 Batchelder, 1991;Batchelder 6 Riefer, 1980;Batchelder, Hu, 6 Riefer, 1994;Batchelder 6 Riefer, 1986;Riefer, Hu, 6 Batchelder, 1994;Batchelder, Riefer, 6 Hu, 1994). studied the entire family of such models and named the family general processing tree (GPT) models (see Hu, 1998b, for other resources about GPT models).…”
Section: Gpt Modelsmentioning
confidence: 99%